PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA SISWA SMPN 8 - Fery Redsidayanti; Martono Martono; Abdussamad Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by the facts in the field that show the results of learning to write news texts have not achieved the expected results. The research method used was descriptive method, the form of research was qualitative, and the type of research was classroom action research (CAR). The research data was processed qualitatively. The results showed that the model of Problem Based Learning (PBL) with the help of audiovisual media could improve the results of learning to write the text of the news. This was evident from the: (1) Planning cycles I and II stages was in compliance with the PBL media audiovisual model, but I cycle there were stages of PBL model has not been noted in RPP and improved cycle II (2) Implementation cycle I've been running well, but there were steps the RPP in learning not yet implemented and improved cycle II (3) the learning outcomes of students has also increased. Study Group on average cycle I and cycle II 67.71 increased to 85.85. Individual learning cycle I average 66.79 and cycle II increased to 85.79. Keywords:Audiovisual Media, Problem Based Learning (PBL) Models, WritingNews Texts